Resposta:
ESPERO TER AJUDADO!!!
Explicação passo-a-passo:
1.
a) x + 6 = 9
x = 9 - 6
x = 3
b) x - 6 = 15
x = 15 + 6
x = 21
c) x + 3 = 0
x = 0 - 3
x = -3
d) 2x + x = 18
3x = 18
[tex]x = \frac{18}{2}[/tex]
x = 9
e) 4x = 16
[tex]x = \frac{16}{4}[/tex]
x = 4
f) x + 9 = 40
x = 40 - 9
x = 31
g) x - 12 = -30
x = -30 + 12
x = -18
h) 5x - 7 = 2x + 2
5x - 2x = 7 + 2
3x = 9
[tex]x = \frac{9}{3}[/tex]
x = 3
i) x + x + x + x = 32
4x = 32
[tex]x = \frac{32}{4}[/tex]
x = 8
j) -x + 11 = -4
-x = -4 - 11
x = -15
k) ESSA EU NÃO SEI
1. Tambem não sei
2.
a) (x + 5) = 0
x = 0 - 5
x = -5
III. x = -5↑
b) (x + 2) = 0
x = 0 - 2
x = -2
IV. x = -2↑
c) 2x + 7 = 9
2x = 9 - 7
2x = 2
[tex]x = \frac{2}{2}[/tex]
x = 1
V. x = 1↑
d) -x + 3 = 7
-x = 7 - 3
-x = 4[tex]-x = 4^{(.1)}[/tex]
x = -4
I. x = -4↑
e) -2x + 4x = 5 = -x + 1
-2x + 4x + x = 5 + 1
3x = 6
[tex]x = \frac{6}{3}[/tex]
x = 2
II. x = 2